From Pandemic to New Normal: Portraying EFL Graduates’ Metacognitive Strategy in Thesis Writing - Rizqiyyah Rizqiyyah; Joko Nurkamto; Dewi Rochsantiningsih (STAI Hubbulwathan Duri, 2021)
The recent paper aims to figure out how students apply their metacognitive strategies of thesis writing in the COVID-19 pandemic. This study employs an explanatory case study design with 13 English As a Foreign language (EFL) graduates of an Indonesian university involving in this study. Questionnaires and semi-structured interview methods were used for collecting information. The data were then qualitatively analyzed using Miles, Huberman, and Saldana interactive model. The findings indicate that individual differences and thesis supervisors' involvement stimulated varied metacognitive strategy use in thesis writing. The challenges, inefficient time management, supervision system, technological issues, and negative disruptive emotions were attributed to delayed thesis completion in the pandemic. It indicates that the metacognitive experience represented by negative psychological factors profoundly affects students’ metacognitive strategies. Hence, promoting students' positive affective states are essential to achieve the expected writing outcomes.